The changing face of law after the events of 1968… or when law meets politics: introduction to the Mouvement Critique du Droit - Kaluszynski, Martine (Oñati Socio-Legal Series, 2012)
The aim of this paper is to analyse the origins, the development and the long-term impact of the Critical Legal Movement (Mouvement Critique du Droit). Created some thirty years ago, this Movement resulted from the collective mobilisation of legal experts and political scientists across French cities (e.g., Lyon, Montpellier, Saint-Etienne, Toulouse and Paris). Referring mainly to Marxist theories, the Critical Legal Movement argued that law is deeply embedded in its social and its political context, and should thus be analysed through an interdisciplinary approach. Building on this critical perspective, the Movement developed a scientific project and teaching methods, which both differed from and opposed the way in which law was traditionally taught and studied in French Law Faculties. The Movement itself no longer exists, but it nevertheless had far-reaching consequences on the study of law. Indeed, the Critical Legal Movement was an opportunity to successfully explore alternative teaching methods and to create high quality research institutions.